Clothed particle representation in quantum field theory: boost generators of the Poincaré group - Korda, V.Yu.; Frolov, P.A. (Вопросы атомной науки и техники, 2007)
The method of the unitary clothing transformations is used to construct the generators of the Poincaré group in the instant form of relativistic dynamics in the second and third orders in the coupling constant. It is shown that the respective algebra of generators is fulfilled up to the sixth order. The relativistic invariance of the mass and vertex corrections derived is proven.